Soft X-Ray EPMA analyses of nanophase lunar Fe-Si compounds - Gopon, Phil; Fournelle, J.; Valley, J.; Horn, W.; Pinard, P.; Sobol, P.; Spicuzza, M.; LLovet, X. (Proceedings of the Wisconsin Space Conference, 2014)
Conventional electron-probe microanalysis (EPMA) has an X-ray analytical spatial resolution on the order of 1-4 Î¼m width/depth. Many of the naturally occurring Fe-Si compounds analyzed in this study are smaller than 1 Î¼m in size, requiring the use of lower accelerating potentials and non-standard X-ray lines for analysis. The problems with the use of low energy X-ray lines (soft X-rays) of iron for quantitative analyses are discussed and a review is given of the alternative X- ray lines that may be used for iron at or below 5 keV (i.e., accelerating voltage that allows analysis of areas of interest smaller than 1 Î¼m). Problems include the increased sensitivity to surface effects for soft X-rays, peak shifts (induced by chemical bonding, differential self- absorption, and/or buildup of carbon contamination), uncertainties in the mass attenuation coefficient (MAC) for X-ray lines near absorption edges, and issues with spectral resolution and count rates from the available Bragg diffractors. In addition to the results from the traditionally used Fe LÎ± line, alternative approaches, utilizing Fe LÎ², and Fe Ll-Î· lines, are discussed.Â